Conducting research with children - Tyree, Wynne (Henry Stewart Talks, 2010)
Importance of conducting research with children and the professional and ethical sensitivities that must accompany it, Segmentation of 'children' into pre-schoolers, kids, tweens and teens and how best to conduct research with each segment, Recommended methods and techniques for each segment, including guidance on successful recruiting, Qualitative and quantitative research methods